A sex-specific effect of M4 muscarinic cholinergic autoreceptor deletion on locomotor stimulation by cocaine and scopolamine - Berezovskaia, Anna; Thomsen, Morgan; Fink-Jensen, Anders; Wörtwein, Gitta (Frontiers in Molecular Neuroscience, 2024)
ObjectiveAcetylcholine modulates the activity of the direct and indirect pathways within the striatum through interaction with muscarinic M4 and M1 receptors. M4 receptors are uniquely positioned to regulate plasticity within the direct pathway and play a substantial role in reward and addiction-related behaviors. However, the role of M4 receptors on cholinergic neurons has been less explored. This study aims to fill this gap by addressing the role of M4 receptors on cholinergic neurons in these behaviors.MethodsTo investigate the significance of M4-dependent inhibitory signaling in cholinergic neurons we created mutant mice that lack M4 receptors on cholinergic neurons. Cholinergic neuron-specific depletion was confirmed using in situ hybridization. We aimed to untangle the possible contribution of M4 autoreceptors to the effects of the global M4 knockout by examining aspects of basal locomotion and dose-dependent reactivity to the psychostimulant and rewarding properties of cocaine, haloperidol-induced catalepsy, and examined both the anti-cataleptic and locomotion-inducing effects of the non-selective anticholinergic drug scopolamine.ResultsBasal phenotype assessment revealed no developmental deficits in knockout mice. Cocaine stimulated locomotion in both genotypes, with no differences observed at lower doses. However, at the highest cocaine dose tested, male knockout mice displayed significantly less activity compared to wild type littermates (p = 0.0084). Behavioral sensitization to cocaine was similar between knockout and wild type mice. Conditioned place preference tests indicated no differences in the rewarding effects of cocaine between genotypes. In food-reinforced operant tasks knockout and wild type mice successfully acquired the tasks with comparable performance results. M4 receptor depletion did not affect haloperidol-induced catalepsy and scopolamine reversal of catalepsy but attenuated scopolamine-induced locomotion in females (p = 0.04). Our results show that M4 receptor depletion attenuated the locomotor response to high doses of cocaine in males and scopolamine in females, suggesting sex-specific regulation of cholinergic activity.ConclusionDepletion of M4 receptors on cholinergic neurons does not significantly impact basal behavior or cocaine-induced hyperactivity but may modulate the response to high doses of cocaine in male mice and the response to scopolamine in female mice. Overall, our findings suggest that M4-dependent autoregulation plays a minor but delicate role in modulating specific behavioral responses to pharmacological challenges, possibly in a sex-dependent manner.